Comparative Characterization of Candidate Molecular Markers in Ischemic and Hemorrhagic Stroke - A. M. Golubev; A. V. Grechko; V. E. Zakharchenko; M. M. Kanarsky; M. V. Petrova; I. V. Borisov (Общая реаниматология)
According to epidemiological studies, the leading cause of morbidity, disability and mortality are cerebrovascular diseases, in particular ischemic and hemorrhagic strokes. In recent years considerable attention has been given to the study of molecular markers of ischemic and hemorrhagic strokes. These studies are relevant because brain-specific protein biomarkers of neurons and glial cells can provide valuable and timely diagnostic information necessary for clinical decision-making.The aim of the study was to reveal the differences in the serum level of molecular markers in acute, subacute and early recovery periods of ischemic and hemorrhagic strokes.Material and methods. The study included 59 patients. Twenty patients were diagnosed with hemorrhagic stroke and 39 had ischemic stroke. The control group included 20 volunteers. Serum levels of molecular CNS markers were determined in acute, subacute, and early recovery stages of stroke. The serum levels of CNS molecular markers of patients with ischemic and hemorrhagic stroke was measured quantitatively by enzyme immunoassay. Statistical analysis was performed by nonparametric Mann-Whitney method.Results. The level of brain-derived neurotrophic factor (BDNF) in the control volunteers was 574.5 [455.5; 615] pg/ml. Significant differences were found for acute and subacute periods of hemorrhagic stroke: it was 674 [560; 749] pg/ml (P=0.003) and 664 [616; 762] pg/ml (P=0.0001).The level of neuron-specific enolase was significantly increased in all periods of the study: it was 4.15 [3.53; 4.8] ng/ml in the control group, 5.4 [4.4; 6.4] ng/ml in acute period of ischemic stroke (P<0.001), 5.4 [4.4; 6.4] ng/ml in early recovery period of ischemic stroke (P=0.001), 5.1 [4.6; 6.4] ng/ml in acute period of hemorrhagic stroke (P=0.014), 664 [616; 762] ng/ml in subacute period of hemorrhagic stroke (P=0.003).In the control group, the serum S-100 protein level was 4.5 [3.8; 5.4] ng/ml. In the acute and early recovery periods of ischemic stroke, S-100 protein level has significantly fallen down to 4.1 [3.4; 4.6] ng/ml (P<0.031) and 3.9 [3.4; 6] ng/ml (P=0.014), respectively. Glial-cell derived neurotrophic factor level was 1.98 [1.64; 2.1] ng/ml in the controls and increased up to 2.4 [2.2; 5] ng/ml (P=0.002) in the acute period and 2.4 [2.3; 2.6] ng/ml (P<0.001) in the subacute period of hemorrhagic stroke.The vascular endothelial growth factor receptor-1 (VEGFR-1) was significantly lower in the subacute period of hemorrhagic stroke: 485 [211; 945] pg/ml in the subacute period vs 903.5 [626; 1115] pg/ml in the controls (P=0.001).Conclusion. We found differences in the serum level of molecular markers in patients with ischemic and hemorrhagic strokes. In the acute period, early recovery period of ischemic stroke, and subacute period of hemorrhagic stroke, there was an increase in the serum level of neuron-specific enolase. The level of brain-derived neurotrophic factor increased significantly in the acute and subacute periods of hemorrhagic stroke. In the acute and early recovery periods of ischemic stroke, the level of S-100 protein decreased. The level of glial cell-derived neurotrophic factor increased in the acute and subacute periods of hemorrhagic stroke. In the subacute period of hemorrhagic stroke, the level of endothelial growth factor receptor-1 significantly decreased. Moreover, there was significant difference between values of this parameter in the subacute period of hemorrhagic stroke and in the early recovery period of ischemic stroke.